Calculation of Artificial Friction Conveying Coefficient f, and a Comparison between ISO and CEMA - Ishwar G. Mulani (Society for Mining, Metallurgy & Exploration, 2004)
In conveyor design, the first step is capacity and the second step is belt width and speed. The third step is decision on 'ff," where distinction arises between DIN/ISO and CEMA for calculating resistances. Then again, both the methods are virtually similar. This topic helps in understanding Dm design style and its comparison to CEMA. This topic is from the book Engineering Science and Application Design for Belt Conveyor wherein the issue has been analysed in detail. It presents a workable calculation model to calculate the value off in design office, based on conveyor parameters. CEMA uses Kx, Ky and 0.01 5 instead off. Thus, f is a sum effect of Kx, Ky and 0.015. Hence, knowledge on f is also applicable to Kx and Ky. This helps to understand their relationship.